Study of Water Quality for Aquaculture System in Ujung Pacu River, North Aceh Regency - Riri Ezraneti; Munawar Khalil; Marzuki Marzuki (Journal Omni-Akuatika, 2020)
Ujung Pacu River is one of the rivers found in North Aceh Regency which is often used by surrounding communities such as for industrial, agricultural, residential and aquaculture activities that can affect river water quality. This study aimed to determine the water physical and chemical parameters in the Ujung Pacu River for aquaculture activities. The research method used was a survey method by determining the sampling station based on community activities around the river. The study consisted of 4 stations with 3 sampling points at each station. Data of water physical and chemical parameters were compared with water quality standards and analyzed descriptively with a quantitative approach. The results showed that the range of water quality values were various in each stations. Ujung Pacu River is influenced by daily tide fluctuations. The highest water quality fluctuations occur in salinity, turbidity and depth. The pollution index in the Ujung Pacu river is included to criteria of Lightly polluted rivers with range 1.8545 - 4.4979. The Ujung Pacu River is unsuitable for aquaculture systems using floating net cages system in river bodies. Keywords: Ujung Pacu River, water quality, pollution index